Trade Research Institutions in Asia-Pacific: Capacity-Building Needs in Developing Countries - Hing Vutha; Larry Strange; K.A.S. Murshid (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2005)
The informal meeting of core Asia-Pacific Research and Training Network on Trade (ARTNeT) research institutions organized by UNESCAP and IDRC in June 2004 in Bangkok highlighted the need for capacity building of research institutions from Least Developed Countries in the region. Llittle research or information is, however, available on what the needs of these research institutions are, their existing trade research capacity and how this differs across countries. This study sets out to address the key following issues: What are the existing trade research capacities of research institutions in LDCs and low-income developing countries in the Asia-Pacific region? What are their capacity-building needs in trade policy research?
Keywords: F1; 330; Research Capacity; LDCs